Tradimento. Come la sinistra liberal stá distruggendo l´America. Coulter, Ann, Milano, Rizzoli, 2004, 358 pág - Hubeñak, Florencio (2004)
Fil: Hubeñak, Florencio. Pontificia Universidad Católica Argentina; Argentina